Ground communities of the Dagestan coast of Caspian Sea in conditions of transgression of the sea and invasy of the Ctenophora Mnemiopsis Leidyi (A. Agassiz) - A. K. Ustarbekov; K. M. Guseynov; A. Sh. Gasanova (Юг России: экология, развитие)
Benthic biocenoses of the Dagestan area of the Caspian Sea were studied. Considered distribution, composition and structure benthic in connection with observed change in environmental conditions. Special attention is given influence Mnemiopsis leidyi (A. Agassiz) on condition zoobenthic.